A Behavioral Genetic Model of the Mechanisms Underlying the Link Between Obesity and Symptoms of ADHD. Issue 10 (August 2020) - Patte, Karen A.; Davis, Caroline A.; Levitan, Robert D.; Kaplan, Allan S.; Carter-Major, Jacqueline; Kennedy, James L.
Objective: The ADHD–obesity link has been suggested to result from a shared underlying basis of suboptimal dopamine (DA); however, this theory conflicts evidence that an amplified DA signal increases the risk for overeating and weight gain. A model was tested in which ADHD symptoms, predicted by hypodopaminergic functioning in the prefrontal cortex, in combination with an enhanced appetitive drive, predict hedonic eating and, in turn, higher body mass index (BMI).Method: DRD2 and DRD4 markers were genotyped. The model was tested using structural equation modeling in a nonclinical sample ( N = 421 adults).Results: The model was a good fit to the data. Controlling for education, all parameter estimates were significant, except for the DRD4-ADHD symptom pathway. The significant indirect effect indicates that overeating mediated the ADHD symptoms–BMI association.Conclusion: Results support the hypothesis that overeating and elevated DA in the ventral striatum—representative of a greater reward response—contribute to the ADHD symptom–obesity relationship.